A Most Remarkable Creature : the hidden life and epic journey of the world's smartest birds of prey - Meiburg, Jonathan (New York : Alfred A. Knopf, 2021)
"An enthralling account of a modern voyage of discovery as we meet a rare and mysterious bird of prey--the caracara--that puzzled Darwin, fascinates modern-day falconers, and carries secrets of our planet's deep past in its family history. In 1833, Charles Darwin was astonished by an animal he met in the Falkland Islands: handsome, social, and oddly crow-like falcons that were "tame and inquisitive... quarrelsome and passionate," and so insatiably curious that they stole hats, compasses, and other valuables from the crew of the Beagle. Darwin wondered why these birds were confined to remote islands at the tip of South America, sensing a larger story, but he set this mystery aside and never returned to it. Almost two hundred years later, Jonathan Meiburg takes up this chase. He takes us through South America, from the fog-bound coasts of Tierra del Fuego to the tropical forests of Guyana, in search of these birds: striated caracaras, which still exist, though they're very rare. He reveals the wild, fascinating story of their history, origins, and possible futures. And along the way, he draws us into the life and work of William Henry Hudson, the Victorian writer and naturalist who championed caracaras as an unsung wonder of the natural world, and to falconry parks in the English countryside, where captive caracaras perform incredible feats of memory and problem-solving. A Most Remarkable Creature is a hybrid of science writing, travelogue, and biography, as generous and accessible as it is sophisticated, and absolutely riveting"--.
new book 2024 fall.
Includes bibliographical references and index.
Keywords: Caracara (Genus); Nature; Bird watching; Animals; Birds